P79. The effect of cognitive reserve in a subcohort of the EMPIR project NeuroMet 'Innovative measurements for improved diagnosis and management of neurodegenerative diseases'. Issue 8 (August 2018) - Göschel, L.; Köbe, T.; Hui, W.; Fillmer, A.; Aydin, S.; Bernd, I.; Flöel, A.
Abstract : Background: One of the most common neurodegenerative diseases is Alzheimer's disease (AD). Maintaining a healthy life style can reduce the risk of AD due to cognitive and brain reserve, but the influence of reserve is often difficult to measure. In this ongoing study, we use 7 T high resolution MRI data from the EMPIR project NeuroMet to explore cognitive reserve in more detail. In NeuroMet, the diverse expertise of various national measurement institutes, including both clinicians and academics, joined together to improve accurate diagnostic and thereby approach better therapy. We present an overview of the project, which aims to (1) develop improved magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) methods, (2) understand bias and uncertainty of immunoassays and digital PCR methods for neurodegenerative disease protein and miRNA biomarkers, (3) develop reference methods for tau, and (4) improve cognitive assessment questionnaire for early diagnosis of Alzheimer's disease. Methods: In this project, a total of 90 participants are being recruited (30 Healthy Control, 30 Mild Cognitive Impairment and 30 AD patients). All subjects are undergoing a battery of neuropsychological tests. With a focus on reserve, the relationship between memory scores and hippocampal volumetric data obtained from T1 weighted MRI images of a 7T MRI scanner (Siemens Magnetom, Erlangen, Germany) will be analyzed. Additionally, participants are being asked to fill in a self-administered lifestyle questionnaire which assesses current physical activity and nutrition. The influence of lifestyle factors will be investigated and preliminary results will be presented. For general blood count and APOE genotyping, blood samples are being drawn. Immunoassays (Meso Scale Discovery) are being developed to overcome matrix effects and achieve duplexed detection of Aß40 and Aß42 within human plasma. Available cerebrospinal fluid (CSF) samples are being tested performing digital PCR for a panel of proteins and miRNA biomarkers, all of which might be used to obtain further insights into cognitive reserve. Furthermore, liquid chromatography mass spectrometry (LC-MS, triple quadrupole and quadrupole time of flight) is performed on blood and CSF samples, to investigate concentrations of the mentioned biomarkers. This diversity of different cutting-edge measures, like ultra-high field MRI and MRS, LC-MS, miRNA assays, new immunoassays, and digital PCR methods, will provide anatomical, functional, and metabolic information in order to improve sensitivity, resolution and delineation for volume, connectivity, and metabolite quantification. Conclusion: The NeuroMet project aims to improve diagnostic measurements for AD, which are important to better understand the effects of cognitive and brain reserve in detail.